2022
DOI: 10.1002/app.53347
|View full text |Cite
|
Sign up to set email alerts
|

A monomolecular organophosphate for enhancing the flame retardancy, thermostability and crystallization properties of polylactic acid

Abstract: Polylactic acid (PLA) is regarded as one of the most promising bioplastics. However, its inherent high flammability of PLA seriously limits its application in the emerging fields. Although the traditional phosphate flame retardants showed excellent flame retardant efficiency in PLA, they often failed to meet the processing requirements of PLA and the thermal stability of PLA composites was decreased after their addition. Herein, an organophosphate flame retardant pentaerythritol bis(phenyl phosphonate) (PBPP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…The PLA/BF-FeP composite showed no change in TSP. Studies are reported in the literature detecting an increase in TSP when phenyl phosphonate FRs are used due to the production of phosphorus free radicals acting in the gas phase. The efficacy of the developed FR coating is noteworthy, given its low loading on the fiber surface, as it successfully mitigated smoke production without compromising its FR capabilities. Consistent with the TGA and MP-AES results, the low FR loading on the fibers does not lead to an appreciable decrease in the mass loss attributable to char production.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The PLA/BF-FeP composite showed no change in TSP. Studies are reported in the literature detecting an increase in TSP when phenyl phosphonate FRs are used due to the production of phosphorus free radicals acting in the gas phase. The efficacy of the developed FR coating is noteworthy, given its low loading on the fiber surface, as it successfully mitigated smoke production without compromising its FR capabilities. Consistent with the TGA and MP-AES results, the low FR loading on the fibers does not lead to an appreciable decrease in the mass loss attributable to char production.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Polylactic acid (PLA) is a kind of thermoplastic polymer produced from lactic acid, which has been successfully utilized in biodegradable material and as a composite matrix material. [30][31][32][33][34] In addition, PLA is a promising and prominent biomaterial that has been widely used to replace the traditional petrochemicalbased polymers in various applications because of the environmental concerns and relatively good mechanical properties. 35 Especially green thermoplastic composites have gained greater attention as ecological consciousness has grown to be more appealing than conventional toxic and nonbiodegradable petroleum-based composites.…”
Section: Introductionmentioning
confidence: 99%
“…Polylactic acid (PLA) is a kind of thermoplastic polymer produced from lactic acid, which has been successfully utilized in biodegradable material and as a composite matrix material 30–34 . In addition, PLA is a promising and prominent biomaterial that has been widely used to replace the traditional petrochemical‐based polymers in various applications because of the environmental concerns and relatively good mechanical properties 35 .…”
Section: Introductionmentioning
confidence: 99%